2020
DOI: 10.1177/0896860819879868
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors of peritoneal dialysis-related peritonitis in elderly patients: A retrospective clinical study

Abstract: Background: This study was to analyze the incidence, risk factors, and clinical outcomes of peritonitis in elderly continuous ambulatory peritoneal dialysis (CAPD) patients. Methods: Incident patients undergone CAPD from 1 January 2006 to 30 June 2015 in our center were enrolled and divided into aged < 65 years and ≥ 65 years groups. Risk factors were evaluated using a logistic regression model, and outcome comparison was evaluated using a Cox proportional model. Results: Among 1953 patients, 111(33.2%) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 28 publications
5
37
0
2
Order By: Relevance
“…Age is also a risk factor of vascular calci cation [17]. Some studies have shown that elderly PD patients are inclined to develop peritonitis [18], but there was no difference in the incidence of peritonitis between elderly and younger group in this study, which was consistent with a Canada study.It was reported that elderly PD patients who were 70 years old or more had no relationship with peritonitis [19], considering that elderly patients had better family,social support and were treated with advanced antibiotics.…”
Section: Discussionsupporting
confidence: 90%
“…Age is also a risk factor of vascular calci cation [17]. Some studies have shown that elderly PD patients are inclined to develop peritonitis [18], but there was no difference in the incidence of peritonitis between elderly and younger group in this study, which was consistent with a Canada study.It was reported that elderly PD patients who were 70 years old or more had no relationship with peritonitis [19], considering that elderly patients had better family,social support and were treated with advanced antibiotics.…”
Section: Discussionsupporting
confidence: 90%
“…Age is also a risk factor of vascular calci cation [15]. Some studies have shown that elderly PD patients are inclined to develop peritonitis [16], but there was no difference in the incidence of peritonitis between elderly and younger group in this study, which was consistent with a Canada study.It was reported that elderly PD patients who were 70 years old or more had no relationship with peritonitis [17], considering that elderly patients had better family social support and was treated with advanced antibiotics.…”
Section: Discussionsupporting
confidence: 90%
“…12,14 Due to these conditions, up to 80% of elderly patients need some degree of assistance while performing PD. [15][16][17][18] The definition of assisted PD varies in literature. 19 In the most liberal way, it is defined as 'a PD modality performed at the patient's home with the help of a healthcare technician, a community nurse, a family member, or a partner'.…”
Section: Introductionmentioning
confidence: 99%